Women space in the design of Masjid in Malaysia: how much space do women need? - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Jahn Kassim, Puteri Shireen (2016)
Malaysian women take women's space in masjid design for granted as a kind of cultural acceptance. So does the architect and the stakeholders in designing according to accepted standards and requirements as a practice from time to time. Currently, not many studies were made on what proportion of the masjid space should be assigned to women. Are current spaces adequate? Is there a rule of thumb for each project or percentage in the design brief for women (and their children/care)? This paper investigates comparatively the allocation of space made for women from the selected masjids in Malaysia, relate them to their actual use as daily prayer space for women and compare to the available standards or practice available. Through a mix-mode method of qualitative and quantitative study, data are collected through a questionnaire survey, observation, physical measurement, interview, and content analysis of existing literature. The study intends to provide a guide to industry players what could specify as ‘rule of thumb’, percentage of space for Malaysian women in masjid design. Findings of surveys from designers/architects had produce some form of consensus on space allocation provided. However, case studies on women’s space as space proportion of each masjid utilised by women on daily prayers ranged drastically across the different states and within each state without any common guide. Immeasurable area of women space, due to the ambiguity of space provision in relation to masjid shape configuration, availability of as-built drawings, historical data of earlier design intentions and time allocated for the study, are the limitations of this study. Women space for daily prayers, as it is, apart from location, shape, amenities and comfort, the capacity is more than adequate. However, majority of these spaces lay in the transit or temporal state of non-permanence for women and their care. Significance of the study disclosed disparity between what is technically planned for women accommodating the rule-of-thumb space allocation to its actual use in the majority of the masjids. To prevent wastage in inappropriateness of space location, a relook to match space utilization to daily and event needs using rule-of- thumb is, therefore, the next agenda.